NORMATIVE ANALYSIS OF PART-TIME P3K POLICY IN THE TEACHER PERSONNEL SYSTEM IN INDONESIA - Risma Latiful Azza; Untung Khoiruddin; Erwin Indrioko (Journal of Governance and Law Reform, 2026)
This study examines the policy concept of part-time Government Employees with Work Agreements (PPPK) within Indonesia’s teacher staffing system. Recent discussions on part-time PPPK have emerged as a response to regional fiscal limitations and the uneven distribution of teachers, yet the legal structure governing civil service employment does not explicitly recognize part-time arrangements for PPPK. The objective of this study is to analyze the normative basis, institutional readiness, and potential implications of implementing a part-time PPPK scheme for teachers. Using a normative legal method supported by a limited policy analysis approach, this research reviews relevant laws, regulatory frameworks, and empirical findings from previous studies. The results indicate that the part-time PPPK model lacks a clear legal foundation, potentially disrupts the standard rights and protections guaranteed to civil servants, and may weaken teacher motivation and job stability. Findings also show that such a scheme could create disparities between regions with different financial capacities and undermine the continuity of instructional duties in schools. In conclusion, this study highlights that part-time PPPK is not aligned with the existing civil service framework and may generate broader administrative and educational challenges. Future studies are encouraged to explore alternative staffing strategies and policy simulations that better support teacher distribution and professional standards